The Fiqh Munakahat Perspective toward Ngalor-Ngulon Tradition in Choosing a Wife Candidate in Banyuwangi Regency - Andre Setiyawan; Miftah Arifin (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
The ngalor-ngulon tradition of the Javanese people in choosing a wife is a prohibition for the Javanese people, especially (men) not to marry women whose house, if pulled straight, forms the direction of ngalor-ngulon (northwest), because it is believed to cause havoc in the household. The focus of this research are: 1) How is the ngalor-ngulon tradition of the Javanese people in choosing a wife? 2) What are the views of community leaders on the ngalor-ngulon tradition of the Javanese community in choosing a wife? 3) How is the ngalor-ngulon tradition seen from the munakahat fiqh? Researchers used a field research model (qualitative) with a descriptive approach model with data collection techniques using three ways, namely: observation, interviews and documentation. The conclusions from this study include: 1) The ngalor-ngulon tradition is a rule for Javanese men not to marry women whose house is on the northwest corner of their house, meaning that Javanese men can marry any woman except the one whose house is ngalor-ngulon. 2) Of the four informants, three of them chose to keep and obey the rules passed down by the ancestors of the Javanese people because these rules had become public law, even though this was not exemplified in religion. 3) Even though this tradition is not mentioned in munakahat fiqh, it is not a violation of religious norms, it only adds to the rules in marriage and is not a violation. Therefore, obeying or violating the ngalor-ngulon tradition does not make the marriage valid or void.